Leadership of School Principals to Improving Teacher Professionalism at Muhammadiyah School - Yusutria Yusutria; Abdul Hopid; Rina Febriana (Al-Misbah (Jurnal Islamic Studies), 2022)
The principal's leadership increases teachers' work motivation and improves education quality. The study examined the principal's leadership in improving teacher professionalism at SD Nitikan Muhammadiyah Yogyakarta. This qualitative descriptive research uses interviews, observation, and documentation. This study involved the principal and 25 teachers as informants. The principal's strategy to improve the quality and professionalism of teachers is to motivate, encourage, and organize training on IT development, reward, and punishment. Principals must also meet content, process, graduation capacity, facilities and infrastructure, management, funding, teacher and staff, and teacher education standards. Supporting factors provide teachers with equal opportunities to develop their pedagogical and professional skills through teaching and training activities based on knowledge and adapted to needs and budgets. Lack of internal motivation from teaching priorities is a barrier. This research contributes to the development of Islamic education by analyzing principals' efforts to increase teachers' professional capacity in Islamic schools.